Factors of poor academic performance in UiTM Arau using fuzzy TOPSIS method / Maisarah Afiqah Nasaruddin - Nasaruddin, Maisarah Afiqah (2021)
The purpose of this study was to rank and analyze the significant factors causing poor academic performance among UiTM students. Motivation, learning attitude, teaching style and learning styles were the selected factors. The study further outlined the criteria for the student when deciding the variables. The method used in this study was Fuzzy Technique for Order Preferences by Similarity to Ideal Solution (FTOPSIS). Followed by the usage of Triangular Fuzzy set to handle the uncertainty. The result of the study showed that FTOPSIS succesfully ranked the factors of poor academic performance as it had different criteria weight. The proposed methodology presents a multi-criteria approach to determine the most common factors the caused the poor academic performance among the UiTM Arau students. The result shows that motivation was the most the nearest approach to the ideal solution with the closest coefficint of 0.7428 while the learning style was the farthest from the ideal solution with the coefficient of 0.1621.